Relationship Between Compliance with the use of Personal Protective Equipment and Work Safety - Rizky Fitri Andini; Iin Ira Kartika; Ummu Habibah; Ira Rahayu (Pusat Riset dan Inovasi Nasional, 2024)
Compliance with the use of Personal Protective Equipment greatly affects work safety, especially health workers who perform actions on patients repeatedly and continuously so that safety during work is determined by compliance in the use of Personal Protective Equipment during service. The purpose of this study was to determine the relationship between compliance with the use of Personal Protective Equipment on the work safety of Health Workers at Bhakti Husada Cikarang Hospital. This study used a cross sectional approach. The population was all health workers who served in the inpatient room at Bhakti Husada Hospital Cikarang in 2024. The research sample used non- random sampling techniques, namely using the total population of 60 people. The results showed a p-value 0.001 (pa = 0.05) and an OR value 8.636, it can be concluded that there is a relationship between compliance with the use of Personal Protective Equipment on occupational safety at Bhakti Husada Cikarang Hospital in 2024. As input to organize special training on the use of Personal Protective Equipment according to its level so that it can be followed by all health workers